2011
DOI: 10.1063/1.3613639
|View full text |Cite
|
Sign up to set email alerts
|

On the effectiveness of CCSD(T) complete basis set extrapolations for atomization energies

Abstract: The leading cause of error in standard coupled cluster theory calculations of thermodynamic properties such as atomization energies and heats of formation originates with the truncation of the one-particle basis set expansion. Unfortunately, the use of finite basis sets is currently a computational necessity. Even with basis sets of quadruple zeta quality, errors can easily exceed 8 kcal/mol in small molecules, rendering the results of little practical use. Attempts to address this serious problem have led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
251
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(265 citation statements)
references
References 123 publications
5
251
0
1
Order By: Relevance
“…The results show that, as it may be expected, QCISD(T) calculations are very close to CCSD(T) ones, with average differences of the order of 0.06 kcal/mol. This error is close to the expected accuracy of CCSD(T) calculations [8,103,110]. Thus, the two methods can be considered equally accurate from the practical point of view.…”
Section: A Equilibrium H· · · H Bond Distancesupporting
confidence: 74%
See 1 more Smart Citation
“…The results show that, as it may be expected, QCISD(T) calculations are very close to CCSD(T) ones, with average differences of the order of 0.06 kcal/mol. This error is close to the expected accuracy of CCSD(T) calculations [8,103,110]. Thus, the two methods can be considered equally accurate from the practical point of view.…”
Section: A Equilibrium H· · · H Bond Distancesupporting
confidence: 74%
“…Such energies can be considered accurate within 1% or ∼0.05 kcal/mol with respect to the true CBS limit [101][102][103] All DFT calculations were performed using the def2-TZVPP basis set [104,105]. The choice of this basis set was dictated by the fact that we wanted to test DFT methods in conditions resembling those used in real applications, where usually very large basis sets are not employed.…”
Section: Computational Detailsmentioning
confidence: 99%
“…A review of extrapolation procedures is beyond the scope of the current work, and interested readers are referred to Ref. [37] and references therein.…”
Section: Correlation Consistent Basis Setsmentioning
confidence: 99%
“…[1][2][3][4][5][6] On the other hand, it has been observed that molecular properties, such as infrared vibrational frequencies and dipole moments, do not necessarily converge smoothly in traditional calculations. [7][8][9][10] The basis set convergence of properties is especially poor in non-augmented cc-p(C)VXZ basis sets.…”
mentioning
confidence: 99%